Graphic Arts (Manga) as a Component of Japanese Cultural Diplomacy Determining Russian and Kazakhstani Consumers’ Behavioral Intentions and Perceived Country Image of Japan (Халықаралық қатынастар және халықаралық құқық сериясы, 2024)
Japanese graphic arts, particularly manga novels, have developed into a global cultural phenomenon, functioning both as a source of entertainment and as a means of influencing perceptions. The majority of research conducted in this field addresses the topic of manga through the lens of soft power and in the context of globalization discourse. This study, however, is focused on determining whether the consumption of Japanese cultural products contributes to the perceived image of Japan, as well as the intentions of people from Russia and Kazakhstan to either travel to Japan or to engage in learning the Japanese language. To estimate the results, the paper employs a computer-based survey to collect descriptive statistics from a sample of 535 individuals. To analyze the data, the authors employed descriptive statistics and a logistic regression model to ascertain the correlation between the respondents’ perceptions of Japan, their consumption of manga, and their likelihood of intending to travel to Japan or to learn the Japanese language. The logistic model evaluation demonstrated that the intention to learn Japanese, the intention to visit Japan, and positive attitudes towards Japan are at least partly shaped by primary Japanese cultural awareness, the amount of money spent on manga-related attributes, and the volume of comics read. Furthermore, the intention to visit Japan is influenced by occupational level, while positive attitudes towards Japan are influenced by the reader's gender. The positive attitude was primarily based on the emotional dimension, as people on average rated the beauty of Japan higher than its political or economic competitiveness and its social values and norms.Key words: consumption of Japanese graphic arts, manga, youth, Russia, Kazakhstan, country image, Japanese culture.